(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Aim: To determine the relationship of different parameters to the method of treatment and type of fractures. Methodology: 50 patients with fractures of the shafts of both the radius and ulna treated at the Vardhman Institute of Medical Sciences, Pawapuri, Nalanda, Bihar, India. Data collection and radiographic measurements were standardized for all patients. All patients were followed at least until bone union occurred or the diagnosis of nonunion was made. These methods of treatment were utilized: open reduction and internal fixation (ORIF), closed reduction with square nailing. End result ratings were made on a 14 point scale in four categories: (a) subjective, according the level of pain in the injured limb; (b) objective, by the range of forearm rotation; (c) radiographic, utilizing the criteria of union, synostosis and malunion. Results: The mean follow-up was 36 months (Range: 3-60 months). Out of 50 patients, 26 were male and 24 were female, with an average age of 28 years (16-45 years). In 31 patients, the fracture involved the dominant limb. 28 of the fractures were open and 22 were closed fractures. Mode of trauma in maximum cases was due to road accidents (n=28), fall from height in 10 patients, Industrial accidents in 6 cases, direct blow in 3 cases and trivial trauma in 3 cases. Overall, 78 % of patients reported no pain, with no difference between patients with open and those with closed fractures. While 80% of patients treated with ORIF were pain free at their last examination, only 56% treated with CR and 48% treated with PIP were painless. There was no significant difference in the loss of forearm rotation between closed and open fractures: 66% of each group lost less than 30 degrees of forearm rotation. Union occurred in 94 percent of radius fractures and 98 percent of ulna fractures, with an average time to union of 18.2 weeks for the radius and 18.6 weeks for the ulna. Conclusion: Treatments of fractures of the shaft of radius and ulna were good to excellent regardless of the method of treatment. Results with ORIF were also found better than CRIF.